The Influence of Weather Factors on Flight Punctuality at Sultan Babullah Airport, Ternate - Rika W., Bintang Rika W.; Fatmawati; Suprapto, Yuyun (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2025)
This study aims to determine the extent to which weather conditions affect flight punctuality at Sultan Babullah Airport in Ternate. Punctuality serves as a key indicator of service quality and operational performance for both airports and airlines. Adverse weather factors such as heavy rain, strong winds, and low visibility often lead to delays. The research employed a quantitative approach with a descriptive-analytical method, involving 71 respondents from airlines, BMKG, and airport staff. Data were analyzed using simple linear regression. The results revealed that weather particularly wind speed and rainfall has a significant impact on delays. The study recommends enhancing inter-unit coordination, utilizing more accurate weather data, and implementing extreme weather mitigation strategies to support smoother flight operations.